Sensory Encounters on Martha’s Vineyard: Native American Deathways in Colonial New England Around 1700 - Brunner, Benedikt (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
On Martha’s Vineyard there was a particularly long-lasting Puritan mission among the Native Americans. This article examines how the clergy there attempted to apply the Puritan ideal of the “visible saints” to the converted Indians and what implications Christianity should have had for their sensory experiences and sensual forms of expression. In a first step, the normative requirements that defined Puritanism around 1700 will be explained on the basis of Cotton Mather’s theology. Dealing with death and dying served as a litmus test for a successful “change of heart.” Using the example of the promotional treatise Indian Converts (1727) by the third-generation missionary Experience Mayhew, who was active on Martha’s Vineyard, the article explores the question of how the senses of hearing and seeing were evaluated in this context. Reading this source against the grain reveals normative conflicts and ambivalences that can deepen our understanding of how coexistence was enabled and to what extent sensory agency was possible for the Native Americans.